The quality of four psychology practice guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE) II. Issue 6 (22nd May 2022) - Trepanier, Lyane; Hébert, Catherine; Stamoulos, Constantina; Reyes, Andrea; MacIntosh, Heather; Beauchamp, Sylvie; Larivée, Serge; Dagenais, Christian; Drapeau, Martin
Abstract: Rationale, Aims and Objectives: Clinical Practice Guidelines (CPGs) have been shown to improve healthcare services and clinical outcomes. However, they are useful resources only to the degree that they are developed according to the most rigorous standards. Multiple studies have demonstrated significant variability between CPGs with regard to specific indicators of quality. The Ordre des psychologues du Québec (OPQ), the College of psychologists of Quebec, has published several CPGs that are intended to provide empirically supported guidance for psychologists in the areas of assessment, diagnosis, general functioning, treatment and other decision‐making support. The aim of this study was to evaluate the quality of these CPGs. Methods: The Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument was used to assess the quality of the CPGs. Results: Our results show that although there have been some modest improvements in quality of the CPGs over time, there are important methodological inadequacies in all CPGs evaluated. Conclusions: The findings of this study demonstrate the need for more methodological rigour in CPGs development as such, recommendations to improve CPG quality are discussed.